Geomorphology and Tourism Potential of the Yerköprü Natural Tunnel, Vezirköprü, Samsun - Faruk Aylar; Serkan Gürgöze; Ali Uzun; Halil İbrahim Zeybek (Coğrafya Dergisi)
In this study, the Yerköprü Natural Tunnel within the boundaries of Küçükkale Village of Vezirköprü district of Samsun province was investigated. This study aims to examine the geomorphological features of this important landform, which has not been studied until now, and to contribute to its introduction. The study was mostly prepared through field observations and measurements. The information collected from the field and the literature was processed in the Geographical Information Systems environment and transformed into maps and diagrams. The Yerköprü Natural Tunnel was excavated from Upper Jurassic–Lower Cretaceous neritic limestones. It has a length of 75 m, a width of 11 m, and a ceiling height of 17 m. The length/height ratio is 4.3. There is a 2-m height difference between the entrance and exit. The creek has a rapid flow through the tunnel and has created numerous potholes. According to the digitized strengths, weaknesses, opportunities, and threats (SWOT) analysis of the use of the tunnel for tourism purposes, the opportunities were high (37%) and the threats were low (14.3%). The Yerköprü Natural Tunnel is one of the most important geomorphosites of the region, together with the Şahinkaya, Kayalı, and Varadoy Canyons and the İncesu fossil bed, which are still frequently visited by nature lovers. Declaring the tunnel and its surroundings as a nature park and opening them to tourism in a controlled manner may contribute to the diversification and sustainability of local tourism.